Kemampuan Menciptakan Nilai Jaringan Digital Pada Ritel Tradisional Kabupaten Kebumen - Joko Fitra; Dani Rizana (SMARTINDO, 2023)
The disruptive era requires all business units to adapt to changes in business models, so as not to be disrupted by digitalization which destroys new business models so that they are able to maintain competitive advantages. In fact, modern retail with the availability of shared resources makes it easier to adapt, compared to traditional retail which has limited shared resources. Another way used by traditional retailers to continue to adapt to the disruptive era is by joining a community that is willing to provide development in the digitalization of the retail business ecosystem. The ability of traditional retail partners to create added value in the digital network business ecosystem in Kebumen Regency is still not optimal. Some of the reasons include pure partnership initiatives coming from corporate partners, the mindset of retail partners is different, the resources owned by retail partners are different (there is no standardization), and the activity links carried out by retail partners are different. Some of the added values created by traditional retail partners include finding guaranteed affordable prices, the opportunity to complete products at outlets, the store atmosphere being neat, clean and bright, involvement in supporting Government policy programs, and an increase in the number of customers and turnover that goes hand in hand with increase in profits